Antimicrobial policies in animals and human health - Boudewijn Catry (BMC, 2017)
Abstract This invited commentary aims to highlight 3 recommendations to rationalize antimicrobial consumption in livestock, in order to minimize the spread of resistant bacteria and simultaneously safeguarding animal and public health.